Modelling tensile tests on high strength S690 steel materials undergoing large deformations. (1st August 2019) - Ho, H.C.; Chung, K.F.; Liu, X.; Xiao, M.; Nethercot, D.A.
Highlights: Full-range true stress-strain curves of S275 and S690 steels up to fracture are measured. Digital image correlation technique is adopted to measure instantaneous dimensions and strain fields in tensile tests. Non-uniform stress and strain distributions across critical cross-sections are found in FE modelling. Iterations are formulated for corrections of full-range true stress-strain curves. Constitutive models for both S275 and S690 steel materials under monotonic actions are proposed. Abstract: Standard tensile tests are commonly used to determine mechanical properties of metallic materials, such as yield strength and tensile strength as well as ductility. In general, these standard tensile tests are able to provide basic mechanical properties of steel materials, commonly referred as engineering stress-strain curves. These curves are considered to be effective for linear elastic and post yielding deformations up to mobilization of tensile strengths, and they are widely adopted in structural design and analysis of steel structures. However, for detailed investigations into structural behaviour of steel structures in large deformations beyond onset of necking, cross-sectional changes in the steel materials often become very large. Hence, an improved stress-strain curve, commonly known as a true stress-strain curve, with proper adjustment according to large longitudinal deformations should be adopted in advanced finite element models. In order to develop full range true stress-strain curves of various steel materials for large deformations, a research project is conducted to perform an integrated experimental and numerical study. Standard tensile tests on two S275 steel coupons and two S690 steel coupons are carried out, and advanced optical measurements using a digital imaging correlation technique are adopted to measure deformation fields of these coupons with a high precision during the entire deformation ranges. After data analyses using three different transformation rules, namely, i) Power Law Method, ii) Linear Law Method, and iii) Instantaneous Area Method, three different true stress-strain curves for each of S275 and S690 steel materials are derived. These curves are then incorporated into advanced finite element models to simulate large deformations of these steel coupons observed in the tensile tests. Improvements to the true stress-strain curves derived from Instantaneous Area Method are made through successive corrections according to measured and predicted deformation characteristics of the steel coupons. Consequently, the proposed true stress-strain curves determined with Instantaneous Area Method are shown to be highly acceptable for numerical analyses of steel structures undergoing large plastic deformations up to fracture. Expressions of the proposed full range true stress-strain curves for S275 and S690 steel materials are also provided.